Palmitoleic acid sensitizes vancomycin-resistant Staphylococcus aureus to vancomycin by outpacing the expression of resistance genes - Zajeba Tabashsum; Michelle Angeles-Solano; Ashelyn E. Sidders; Joshua B. Parsons; Sarah E. Rowe (Microbiology Spectrum)
ABSTRACT The rise in antibiotic resistance limits the availability of antibiotics to treat bacterial infections. Despite this, antibiotic development pipelines remain sparse which makes using adjuvants to reverse antibiotic resistance a promising therapeutic strategy. The use of vancomycin, a frontline antibiotic used to treat hospitalized patients with methicillin-resistant Staphylococcus aureus (MRSA) infections, is complicated by high rates of treatment failure. Vancomycin binds to the D-ala-D-ala terminus of the nascent peptidoglycan precursor lipid II, preventing cell wall biosynthesis. Vancomycin-resistant strains of S. aureus and Enterococci typically express a van gene cluster that is induced in response to vancomycin and results in the synthesis of an alternative lipid precursor with a peptide chain ending in D-ala-D-lac. Vancomycin has low affinity for the D-ala-D-lac terminus, and the bacteria can resume growth even in the presence of an otherwise lethal dose of vancomycin. We previously showed that palmitoleic acid, a host-produced monounsaturated fatty acid, combined with vancomycin led to an accumulation of large fluid patches in the bacterial membrane, resulting in membrane destabilization and cell death. In this study, we observed that palmitoleic acid increases the rate of vancomycin killing by more than 50-fold, compared to vancomycin alone. This rapid bactericidal activity by the combined treatment sensitized vancomycin-resistant S. aureus (VRSA) and vancomycin-resistant Enterococcus (VRE) to vancomycin, likely by outpacing the expression of vancomycin resistance genes. This study represents an important step in the ongoing effort to mitigate antibiotic resistance.IMPORTANCEThe development of antibiotics has transformed medicine, reducing the incidence and severity of bacterial infections and allowing for advancements in healthcare, including invasive surgeries and organ transplants. However, the rise of antibiotic resistance poses a significant threat to these medical advancements, leading to treatment failures that result in increased patient morbidity and mortality, as well as substantial healthcare costs. Vancomycin-resistant Enterococcus (VRE) species are prevalent in hospital settings and chronic infections. Although high-level vancomycin resistance in S. aureus is rare, S. aureus can acquire plasmids expressing vancomycin resistance genes from resistant Enterococcal species during infection, further complicating treatment. In this study, we find that palmitoleic acid increases the rate of vancomycin killing and restores sensitivity to vancomycin-resistant S. aureus (VRSA) and VRE isolates.